Disparities in Palliative Care Utilization Among Hospitalized People With Huntington Disease: A National Cross-Sectional Study. (May 2022) - Sokol, Leonard L.; Bega, Danny; Yeh, Chen; Kluger, Benzi M.; Lum, Hillary D.
Background: People with Huntington's disease (HD) often become institutionalized and more frequently die away from the home setting. The reasons behind differences in end-of-life care are poorly understood. Less than 5% of people with HD report utilization of palliative care (PC) or hospice services, regardless of the lack of curative therapies for this neurodegenerative disease. It is unknown what factors are associated with in-patient specialty PC consultation in this population and how PC might be related to discharge disposition. Objectives: To determine what HD-specific (e.g., psychosis) and serious illness-specific factors (e.g., resuscitation preferences) are associated with PC encounters in people with HD and explore how PC encounters are associated with discharge disposition. Design: We analyzed factors associated with PC consultation for people with HD using discharge data from the National Inpatient Sample and the Nationwide Inpatient Sample (NIS), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality. An anonymized, cross-sectional, and stratified sample of 20% of United States hospitalizations from 2007 through 2014 were included using ICD-9 codes. Results: 8521 patients with HD were admitted to the hospital. Of those, 321 (3.8%) received specialty PC. Payer type, (specifically private insurer or other insurer as compared to Medicare), income, (specifically the top quartile as compared to the bottom quartile), mortality risk, D.N.R., aspiration pneumonia, and depression were significantly associated with PC in a multivariate model. Among those who received PC, the odds ratio (OR) of discharge to a facility was 0.43 (95% CI, 0.32-0.58), whereas the OR of discharge to home with services was 2.25 (95% CI 1.57-3.23), even after adjusting for possible confounders. Conclusions: Among patients with HD, economic factors, depression, and serious illness-specific factors were associated with PC, and PC was associated with discharge disposition. These findings have implications for the adaptation of inpatient PC models to meet the needs of persons with HD.